2014
DOI: 10.4103/0255-0857.136553
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis C virus RNA in peripheral blood mononuclear cells of patients with abnormal alanine transaminase in Ahvaz

Abstract: In the present study high rate of 32% occult hepatitis C were found among the patients with elevated ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Patients with long-term persistent ALT abnormality or with the lack of overt viral detection and autoimmune markers, have been shown to be positive for HBV DNA (OBI)[ 114 ]. While the etiology of cryptogenic liver disease remains unknown, the association of occult hepatitis C has been reported in patients with abnormal alanin aminotransaminase[ 115 ]. OBI has been regarded as an additional risk factor for progression of liver cirrhosis and HCC[ 26 , 116 ].…”
Section: Obi and Cryptogenic Liver Diseasementioning
confidence: 99%
“…Patients with long-term persistent ALT abnormality or with the lack of overt viral detection and autoimmune markers, have been shown to be positive for HBV DNA (OBI)[ 114 ]. While the etiology of cryptogenic liver disease remains unknown, the association of occult hepatitis C has been reported in patients with abnormal alanin aminotransaminase[ 115 ]. OBI has been regarded as an additional risk factor for progression of liver cirrhosis and HCC[ 26 , 116 ].…”
Section: Obi and Cryptogenic Liver Diseasementioning
confidence: 99%
“…9 OBI and OCI have attracted more attention recently, since they appear to be related to the progressed liver fibrosis and cirrhosis. 19 (0.25%) 20 and Thailand (18.2%) 21 ; in people with glomerular nephropathies in Spain (39.0%) 22 ; in people with cryptogenic liver disease in Iran (10.1%), 10 Spain (57.0%), 9 and Pakistan (74.0%) 23 ; in those with HIV infection in Georgia (10.2%) 13 and Iran (9.2%) 24 ; in people with HBV infection (28%) in Italy 25 ; among those with HCC in Italy (40.0%) 23 ; in individuals with elevated ALT (32%) in Iran 26 ; in patients with lymphoproliferative disorders (20%) in Egypt 27 and Spain (13.3%) 28 ; in individuals with various hematological disorders in Egypt (20%) 29 ; in individuals with kidney transplantation (0.5%) in Germany 20 and Egypt (3.7%) 30 ; in general population in Italy (3.3%) 31 ; and in volunteer blood donors in China (2.2%). 32 Therefore, there are numerous reports of the presence of OCI in different groups of people worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Iran showed the increased level of ALT in patients with OCI. 26 In Thailand, the high prevalence of HBV and HCV infection in HIV-infected Thai patients has reported. Male sex, elevated serum ALT levels, and low CD4 percentage are associated with coinfection of HBV and HCV and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18] Since the first description of OCI 8 many data supporting the presence of OCI in specific populations such as in HD and patients with cryptogenic liver cirrhosis. 12,19,20 Meanwhile, others have reported absence of OCI in patients with immunosuppressive conditions and HCV-associated diseases. [21][22][23] Nonetheless, the contribution of this extrahepatic reservoir could have clinical consequences in viral transmission and disease pathogenesis, thus, future studies are needed to add to our knowledge of the OCI clinical significance.…”
Section: Discussionmentioning
confidence: 99%